Pharmacological Profile of KUL-7211, a Selective -Adrenoceptor Agonist, in Isolated Ureteral Smooth Muscle - Yoshitaka Tomiyama; Makoto Murakami; Kohichi Hayakawa; Katsuyoshi Akiyama; Yoshinobu Yamazaki; Masami Kojima; Nobuo Shibata; Masuo Akahane (Elsevier, 2003)
Since, in the human ureter, both β2- and β3-adrenoceptors mediate adrenergic-stimulation-induced relaxation, selective β2-/β3-adrenoceptor agonists might prove clinically useful for relieving ureteral colic and promoting stone passage. We evaluated the β-adrenoceptor subtype selectivity and ureteral-relaxing efficacy of (-)-2-[4-(2-{[(1S,2R)-2-hydroxy-2-(4-hydroxyphenyl)-1-methylethyl]amino}ethyl)phenyloxy]acetic acid (KUL-7211), a new β-adrenoceptor agonist, in vitro. In rat isolated organs, its selectivities, for inhibition of spontaneous uterine contraction (mediated via β2-adrenergic stimulation) and inhibition of colonic contraction (via β3-adrenergic stimulation) versus increase in atrial rate (via β1-adrenergic stimulation), were 56.3 and 242.2, respectively. KUL-7211 relaxed 80-mM-KCl-induced tonic contractions in both rabbit (pD2 value: 5.86 ± 0.13, whose ureteral relaxation is mediated via β2-adrenergic stimulation) and canine (pD2 value: 6.52 ± 0.16, via β3-adrenergic stimulation) isolated ureters in a concentration-dependent manner. These KUL-7211-induced relaxing effects were antagonized by ICI-118,551 (selective β2-adrenoceptor antagonist, pKB value: 8.91 ± 0.24) in the rabbit ureter and by bupranolol (non-selective β-adernoceptor antagonist, pKB value: 6.85 ± 0.12) in the canine ureter. KUL-7211 also reduced the spontaneous rhythmic contraction in a canine ureteral spiral preparation in a concentration-dependent manner, the pD2 value being 6.83 ± 0.20. These data clearly demonstrate that KUL-7211 selectively stimulates both ureteral β2- and β3-adrenoceptors and potently relaxes ureteral smooth muscle. KUL-7211 may be a novel and useful medication for relieving ureteral colic and promoting stone passage in urolithiasis patients.